Case report of cutaneous histiocytic sarcoma: diagnostic and therapeutic dilemmas - Flavia Trevisan; Celia Antonia Xavier; Clovis Antonio Lopes Pinto; Fernanda Gomes Cattete; Fabiola Schauffler Stock; Marcella Ledo Martins (Sociedade Brasileira de Dermatologia, 2013)
Histiocytic sarcoma is a rare hematologic malignant neoplasia originating from histiocytic or dendritic cell clones. The lesions may be in nodal or extranodal sites, most commonly in the gastrointestinal tract. A small number of cases presents as unique cutaneous lesions. The definitive diagnosis is made by positivity for the immunohistochemical markers CD163, CD68, CD4 and lysozyme. The treatment is controversial, often with combined systemic chemotherapy. This is a case of cutaneous histiocytic sarcoma in an 82-year-old patient presenting two nodular lesions in the breast and right arm which were treated with simple excision and multidisciplinary follow-up, avoiding aggressive management and exhaustive investigations. Although most studies report aggressive evolution, the patient had good and stable clinical status during the twelve-month follow-up period.